2021
DOI: 10.1002/rrq.427
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Story Read‐Aloud Lessons on Literacy Development in the Early Grades: Experimental Evidence From Nigeria

Abstract: Research has indicated that reading aloud to young students can enhance their foundational reading skills and their reading motivation, but such research has been lacking in African contexts. In this study, we assessed the efficacy of story read-aloud lessons in improving students' foundational reading skills in Nigeria. The experiment took place in a cluster randomized trial of 199 schools in Northern Nigeria. In treatment schools, second-grade teachers conducted weekly read-aloud lessons as an addition to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
0
5
0
3
Order By: Relevance
“…Modelling is another instructional strategy that has been shown to be particularly successful at promoting student learning gains (Purdiyanto et al, 2021), motivation (Moussa and Koester, 2021) and self-regulation (Schunk and Zimmerman, 2007), which are central to students' learning process (Checa et al, 2008). Westbrook et al's (2013) rigorous literature review of pedagogic practices that best support all students learning at both primary and secondary levels in low-income countries, for example, identified demonstration as a key teaching strategy associated with positive student outcomes.…”
Section: Lesson Facilitationmentioning
confidence: 99%
See 1 more Smart Citation
“…Modelling is another instructional strategy that has been shown to be particularly successful at promoting student learning gains (Purdiyanto et al, 2021), motivation (Moussa and Koester, 2021) and self-regulation (Schunk and Zimmerman, 2007), which are central to students' learning process (Checa et al, 2008). Westbrook et al's (2013) rigorous literature review of pedagogic practices that best support all students learning at both primary and secondary levels in low-income countries, for example, identified demonstration as a key teaching strategy associated with positive student outcomes.…”
Section: Lesson Facilitationmentioning
confidence: 99%
“…Moreover, Hattie (2009) synthesised over 800 meta-analytic studies of various designs and found that learning activities where the teacher is actively involved with the lesson (for example, working through the problem step by step with the students) are particularly effective at promoting learning gains in students, compared with activities where the teacher is less involved (for example, the teacher instructing students to complete a problem sheet independently). Research from Nigeria has also pointed to the positive impacts that teacher modelling of reading aloud can have on primary pupils' listening comprehension, letter sound recognition, non-word decoding and reading fluency, along with their motivation to read (Moussa and Koester, 2021). Further, by thinking aloud and walking students through thought processes, they will then be able to take a similar approach to solving similar problems on their own.…”
Section: Lesson Facilitationmentioning
confidence: 99%
“…These activities allow parents to read stories aloud (Epstein, 2018). The study of Moussa and Koester (2021) indicated that reading a story or context aloud enhances a learner's fundamental reading skills and develops the learner's reading motivation. The fifth type of parental involvement is decision-making.…”
Section: Related Literature and Studiesmentioning
confidence: 99%
“…In the Nordic context, researchers have noted that Nordic language arts curricula foreground language and literacy skills in relation to literature teaching ( Gourvennec et al, 2020 ;Liberg et al, 2012 ), leading to an emphasis on literary texts as a resource for developing literacy skills. Studies have highlighted the use of literary texts to foster disciplinary skills of analysis and interpretations ( Moore & Schleppegrell, 2014 ;Spires et al, 2018 ), genre-specific writing skills ( Gabrielsen et al, 2019 ;Moore et al, 2018 ;Walldén, 2021 ), as well as generic literacy skills ( Moussa & Koester, 2021 ). Some of the cited studies express concerns that the use of literature is subsumed under the literacy paradigm ( Gabrielsen et al, 2019 ;Gourvennec et al, 2020 ;Liberg et al, 2012 ), while others show that an explicit focus on language and text structures may promote meaningful engagements with texts ( Moore et al, 2018 ;Walldén, 2021 ).…”
mentioning
confidence: 99%